2022
DOI: 10.1590/1678-4685-gmb-2021-0378
|View full text |Cite
|
Sign up to set email alerts
|

A novel PRRX1 loss-of-function variation contributing to familial atrial fibrillation and congenital patent ductus arteriosus

Abstract: Atrial fibrillation (AF) represents the most common type of sustained cardiac arrhythmia in humans and confers a significantly increased risk for thromboembolic stroke, congestive heart failure and premature death. Aggregating evidence emphasizes the predominant genetic defects underpinning AF and an increasing number of deleterious variations in more than 50 genes have been involved in the pathogenesis of AF. Nevertheless, the genetic basis underlying AF remains incompletely understood. In the current researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In addition, Ke et al reported a family with a PRRX1 heterozygous mutation that resulted in familial PDA and atrial fibrillation caused by PRRX1 loss of function. The family is at a significantly increased risk of stroke ( 99 ). In conclusion, the relationship between VSD and PDA and brain diseases is still unclear, but it should be considered in clinical practice that VSD and PDA may be the etiology or risk factors for some difficult neuropsychiatric cases.…”
Section: Left-to-right Shunt and Brain Diseasesmentioning
confidence: 99%
“…In addition, Ke et al reported a family with a PRRX1 heterozygous mutation that resulted in familial PDA and atrial fibrillation caused by PRRX1 loss of function. The family is at a significantly increased risk of stroke ( 99 ). In conclusion, the relationship between VSD and PDA and brain diseases is still unclear, but it should be considered in clinical practice that VSD and PDA may be the etiology or risk factors for some difficult neuropsychiatric cases.…”
Section: Left-to-right Shunt and Brain Diseasesmentioning
confidence: 99%
“…This leads to increased myocardial contractility and heart rate, which can cause left congestive heart failure, which can progress to pulmonary edema, atrial fibrillation, moderate pulmonary hypertension secondary to left congestive heart failure and mitral regurgitation secondary to left ventricular dilation. [4][5][6]…”
Section: Introductionmentioning
confidence: 99%
“…Genetic defects responsible for CHD include aneuploidy (presence of an additional chromosome, absence of a chromosome, or deletion/duplication of one arm of a chromosome), copy number variation (deletion or duplication of a segment of a chromosome), and genetic mutations [ 44 , 45 , 46 ]. To date, pathogenic mutations in over 100 genes have been involved in the occurrence of CHD, of which most encode cardiac transcription factors, cell adhesion molecules, signaling pathway proteins, and cardiac structural proteins essential for cardiovascular morphogenesis [ 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. However, CHD is of pronounced genetic heterogeneity, and the genetic determinants causative for CHD in a significant proportion of cases remain to be identified.…”
Section: Introductionmentioning
confidence: 99%